Estimating the elasticity of consumer prices to the exchange rate: An accounting approach - Hadrien Camatte; Guillaume Daudin; Violaine Faubert; Antoine Lalliard; Christine Rifflart (European Central Bank (ECB), 2021)
We analyse the elasticity of the household consumption expenditure (HCE) deflator to the exchange rate, using world input-output tables (WIOT) from 1995 to 2019. In line with the existing literature, we find a modest output-weighted elasticity of around 0.1. This elasticity is stable over time but heterogeneous across countries, ranging from 0.05 to 0.22. Such heterogeneity mainly reflects differences in foreign product content of consumption and intermediate products. Direct effects through imported consumption and intermediate products entering domestic production explain most of the transmission of an exchange rate appreciation to domestic prices. By contrast, indirect effects linked to participation in global value chains play a limited role. Our results are robust to using four different WIOT datasets. As WIOT are data-demanding and available with a lag of several years, we extrapolate a reliable estimate of the HCE deflator elasticity from 2015 onwards using trade data and GDP statistics.
Keywords: C67; E31; F42; F62; 330; input-output linkages; spillovers; global value chains; cost-push inflation